Direct observation of drifting juvenile seahorse Hippocampus trimaculatus Leach, 1814 beneath the offshore surface at Malacca Strait - Wong, Nur Leena Wai Sin; Teh, Jun Chin (Pensoft Publishers, 2017)
Three drifting juvenile seahorses (100.3 mm, 89.5 mm, and 55.8 mm in height) were captured during 2 research surveys between shipping routes at Malacca Strait. All seahorse specimens were identified using morphometric data as Hippocampus trimaculatus Leach, 1814. This is the first direct observation of drifting H. trimaculatus seahorse near to the water surface, out of their reported water depth (10–100 m) and demersal habitats. This may provide evidence of translocation and long-distance dispersal of H. trimaculatus in the region.